Persepsi tentang Pandemi COVID-19 dan Dampak Kesehatan yang dirasakan; Perspektif Gender pada Kelompok Pekerja Pariwisata - Ratu Matahari; Helfi Agustin; Fitriana Putri Utami (Jurnal Kesehatan Komunitas, 2021)
Workers in the tourism sector automatically lose their jobs due to restrictions on mobility and a ban on gatherings during the pandemic. The pandemic has caused mental health problems due to the economic breakdown, distance from social life and loss due to the death of family members. This qualitative study aims to analyze perceptions and the perceived health impacts of COVID-19 pandemic and on tourism workers in Yogyakarta. The approach used is a case study, conducted in June-September 2021. Female and male informants were involved to see if there were differences in the gender perspective. Survivors and non-survivors were involved to see differences in perceptions. The number of informants consists of 8 people, using the principles of adequacy and suitability. In-depth interviews were conducted online (phone whats app and google meet). Data were analyzed using content analysis method. The results of the study found that the economic impact was felt equally by male and female workers. Gender differences do not affect the decision of superiors when reducing employees and reducing working hours. There is no psychological pressure due to the inequalities of communication between men and women in financial management. There are no complaints of family nutritional insecurity in women because they still get enough nutrition and food, and there is also no gender-based violence at home or at work. The psychological and social impacts were not evident for women, but were found in male informants who were shown to be reluctant to socialize because they were ashamed of losing their jobs. This research is expected to contribute to gender-based policies for handling pandemics and workers in the non-formal tourism sector.